2015
DOI: 10.2196/mhealth.3929
|View full text |Cite
|
Sign up to set email alerts
|

Using a Mobile App for Monitoring Post-Operative Quality of Recovery of Patients at Home: A Feasibility Study

Abstract: BackgroundMobile apps are being viewed as a new solution for post-operative monitoring of surgical patients. Mobile phone monitoring of patients in the post-operative period can allow expedited discharge and may allow early detection of complications.ObjectiveThe objective of the current study was to assess the feasibility of using a mobile app for the monitoring of post-operative quality of recovery at home following surgery in an ambulatory setting.MethodsWe enrolled 65 consecutive patients (n=33, breast rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
179
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(191 citation statements)
references
References 24 publications
12
179
0
Order By: Relevance
“…Potential data security and privacy breaches are an increasing concern in mobile medicine. (8,9) One study identified potential data security and privacy breaches in 95.63%, 17,193/17,979 of mobile iOS apps. (10) In our project, patient confidentiality and data security were built into the design from the beginning, starting with the hospital firewall for data repository and with the use of protected institutional emails.…”
Section: Resultsmentioning
confidence: 99%
“…Potential data security and privacy breaches are an increasing concern in mobile medicine. (8,9) One study identified potential data security and privacy breaches in 95.63%, 17,193/17,979 of mobile iOS apps. (10) In our project, patient confidentiality and data security were built into the design from the beginning, starting with the hospital firewall for data repository and with the use of protected institutional emails.…”
Section: Resultsmentioning
confidence: 99%
“…Other mHealth studies considered the usability and receptiveness of application-based tools using different forms of Likert scales [2,7] or qualitative measures from patient responses [5,6] to find important associations related to application quality and user opinions. These studies assessed a variety of health interventions and most had positive results when investigating topics such as usability [3] and acceptability [2,7].…”
Section: Discussionmentioning
confidence: 99%
“…These studies assessed a variety of health interventions and most had positive results when investigating topics such as usability [3] and acceptability [2,7]. Unlike previous studies, this study quantified comfort with using smartphone functions and examined correlates of those changes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2;2018 Moreover, it is also suggested that the use of mobile applications can be highly feasible in healthcare sector. The recipients of the technology are showing high acceptance level and recommending the future use of mobile applications support (Semple, et al 2015). Similarly, Browning, et al (2016) conducted a research to examine the role of mobile technology in healthcare sector.…”
Section: Literature Reviewmentioning
confidence: 99%